Analysis of the image of stigma against covid-19 sufferers - Adri Idiana (Science Midwifery, 2022)
The violent COVID-19 pandemic and mode of transmission have created fear in the community, potentially leading to social stigma. Social stigma or negative associations with individuals or groups with symptoms or with certain medical conditions. they are labelled Stereotype, discrimination, discrimination and/or identity harassment related to illness. Stigma actually causes disease to spread Society is spinning out of control. This study is a systematic review using online databases namely Scholar, ScienceDirect, and ProQuest. The keywords used were image Stigma, against, COVID-19.,sufferers. The selection process used the PRISMA protocol, resulting in 15 articles that met the inclusion criteria. When the COVID-19 pandemic emerged, stigma was based on a lack of public knowledge, supplemented by unsubstantiated information or uncontrolled fake news, leading to excessive public attention and fear, leading to misunderstandings and discriminatory treatment. Health workers bar COVID-19 survivors from leaving their homes, even refusing to bury bodies. Stigma not only affects the mentality of those who are discriminated against, but has the potential to create negative motivations in vulnerable communities by not adopting healthy behaviors or even concealing their illnesses, creating connections that identify barriers and contribute to increased COVID-19 mortality. Effective preventive measures can be taken to minimize stigma, provide education or awareness-raising in the form of community health campaigns and outreach, and screen false reports so the public can obtain information from reliable official sources. Factors contributing to the public's stigma against COVID-19 are the level of knowledge that affects individuals' perceptions and actions, as well as the spread of untrustworthy information. Stigma can take the form of discriminatory treatment, labelling and stereotyping. The impact of stigma on COVID-19 can create barriers to contact tracing, lead to case reporting and stress, and potentially lead to mental health issues. Prevention of COVID-19 can be achieved by providing education, health promotion, providing credible information and controlling false reporting, and providing psychological support counseling for those stigmatized by society.